Stress Tensor of Free Maxwell Field in Friedmann-Robertson-Walker Universe - Sharma, SK; Dhungel, PR; Khanal, U (Scientific World, 2010)
The solutions of the Maxwellian field in FRW spacetime, found by using the Newman Penrose formalism, is used to determine the energy-momentum tensor. The tensor is obviously traceless, with the energy density equal to the sum of the radial and the two tangential pressures. But it turns out that the radial and tangential pressures are not equal, giving rise to anisotropy. Such anisotropy can be the origin of the rotation of galaxies. Another result is that the photon energy in a closed universe are quantized in units of one from the lowest value of two upwards. The lowest quantum of two can be interpreted as one unit of spin energy and one of translational energy. Key words: Galactic structure; Maxwellian field; Anisotropic pressure. DOI: 10.3126/sw.v7i7.3814 Scientific World Vol.7(7) 2009 pp.1-2